2012
DOI: 10.1007/s10339-012-0482-8
|View full text |Cite
|
Sign up to set email alerts
|

The language of landmarks: the role of background knowledge in indoor wayfinding

Abstract: To effectively wayfind through unfamiliar buildings, humans infer their relative position to target locations not only by interpreting geometric layouts, especially length of line of sight, but also by using background knowledge to evaluate landmarks with respect to their probable spatial relation to a target. Questionnaire results revealed that participants have consistent background knowledge about the relative position of target locations. Landmarks were rated significantly differently with respect to their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…However, each of these tools needs to be clearly seen and labeled. This finding supports previous research by Frankenstein et al (2012), where wayfinders wanted clear sight lines to assist in wayfinding. Service desks that were clearly visible were accessed most often.…”
Section: Discussionsupporting
confidence: 94%
“…However, each of these tools needs to be clearly seen and labeled. This finding supports previous research by Frankenstein et al (2012), where wayfinders wanted clear sight lines to assist in wayfinding. Service desks that were clearly visible were accessed most often.…”
Section: Discussionsupporting
confidence: 94%
“…Regarding people, research has demonstrated that background knowledge influences decisions in wayfinding (Cornell and Heth 2000;Frankenstein et al 2012). Furthermore, people with a good self-reported sense of direction rate survey descriptions higher, and spatial (mental rotation) ability is negatively correlated with wayfinding errors and positively with rating of survey directions (Padgitt and Hund 2012).…”
Section: Route-planning Supportmentioning
confidence: 98%
“…Mobile route guidance is significant for operators in the maintenance process when a building is complex and has restricted areas (Frankenstein et al 2012). Traditionally, workers rely on memory, signs and building plan maps to find a route to destination step-by-step.…”
Section: Mobile Route Guidancementioning
confidence: 99%